Nutrient profile of five freshwater fish species (SAARC Journal of Agriculture, 2019)
The nutrient profile of five freshwater fish species viz., Mystus vittatus, Ompok bimaculatus, Channa striata, Wallago attu and Pangasianodon hypophthalmus were studied. The proximate composition data shows that the moisture and fat content differed significantly (P